(untitled) (Journal of Advanced Veterinary and Animal Research, 2024)
Objective: The study aimed to assess the feasibility of incorporating food-grade zinc sulfate (ZnSO4 ) for making zinc-fortified meatballs from broiler meat. Materials and Methods: A total of 20 broiler breasts were treated with different concentrations of elemental zinc (Zn) of food-grade ZnSO₄ for making meatballs. The study included a control group without added Zn (T0: 0 mg/kg) and treatment groups with Zn concentrations of 10 mg/ kg (T1), 20 mg/kg (T2), 30 mg/kg (T3), and 40 mg/kg (T4). Post-cooking, the meatball samples underwent preservation at −20°C for proximate composition, quality parameters, storage quality, texture, and sensory analysis. Results: Though the moisture content of meatballs did not differ significantly (p > 0.05), the T4 meatballs showed higher moisture percentages and significantly (p < 0.01) higher crude protein content compared to the control. However, a significant increase in cook yield (p < 0.01) and water-holding capacity (p < 0.05) were revealed by the T4 group. The T4 meatball recovered around 41.8% Zn. The malondialdehyde levels in all samples were acceptable when kept in the chiller for ten days. Moreover, the addition of varying doses of ZnSO4 did not result in a significant alteration (p > 0.05) in the hardness of the meatballs. The sensory panelists also validated the instrumental outcome of hardness. Conclusion: The addition of 40 mg/kg of elemental Zn from ZnSO4 improves nutritional composition and quality with no alteration of the texture and sensory properties of the meatball. This dose could be an effective strategy for fortifying chicken meat products and could offer a valuable source of dietary Zn for human consumption. J. Adv. Vet. Anim. Res., 11(4): 1130–1138, December 2024 http://doi.org/10.5455/javar.2024.k864